Doctor, my child is bullied: food allergy management in schools. Issue 3 (June 2016) - Egan, Maureen; Sicherer, Scott
Abstract : Purpose of review: Studies suggest that food allergies have increased in prevalence, resulting in most school classrooms having more than one child affected. Children with food allergies are vulnerable for experiencing potentially life-threatening allergic reactions, as well as social consequences such as bullying. Management recommendations for food allergies in schools should incorporate knowledge of both issues. Recent findings: Current recommendations for food allergy management in schools focus on appropriate avoidance measures and prompt recognition and treatment of allergic reactions. Guidelines focus upon a school-wide approach, with comprehensive involvement of many stakeholders, but individual students require specific emergency action plans. Special risk groups include young children who need additional supervision and adolescents who may take risks. Based on the observation that anaphylaxis can occur in persons without a prior diagnosis, having epinephrine available for prompt first-aid management of any student in need is now recommended. To promote socialization, avoidance measures should minimize separation of children with food allergies from their peers. Parents and schools need to be aware of bullying and implement intervention and prevention measures. Summary: Management recommendations for food allergies in schools should ensure the safety of the child, address bullying, and avoid unnecessary isolation.